Reported child abuse and neglect in Cape Town - Lachman, Peter Irwin (Department of Paediatrics and Child Health, 2018)
The problem: The study of child abuse in South Africa has concentrated on management issues, and the epidemiology of child abuse and neglect has yet to be determined. Child abuse intervention programmes are based on data from studies conducted in the United States and Europe. Over the past few years practitioners in the field have expressed the need for local information to be available in order to plan future child protection programmes. A review of the literature reveals that the medico-legal model developed in the United States and the United Kingdom, based on investigation, is under strain due to the large number of reported cases of child abuse. Aims: The study aims to compare the data collected with that reported in the literature. The specific research questions include: • Can the characteristics of abused children in Cape Town be determined? • Do the characteristics of child abuse and neglect in Cape Town differ from those reported in the literature? • Should and can a child abuse reporting system be developed and implemented? • Can prevention and intervention strategies be developed based on the epidemiological data that has been collected? • Can the study in Cape Town provide an impetus for further research in the field of child abuse and neglect? • Can the results provide the basis for a National Plan of Action on child abuse and neglect? Methodology Following extensive consultation in with professionals and practitioners in the field, a child abuse reporting system was established in Cape Town, South Africa. Clear definitions of child abuse and neglect were agreed upon, and for the period October 1993 to May 1995 practitioners in the field reported all cases of child abuse and neglect to a central reporting centre. The data was entered on to a computer and analysed by the researcher. Results • The overall picture of child protection in Cape Town: • Child abuse and neglect primarily affects females in the Cape Town area; • younger children are more likely to be physically abused or neglected; • older children are more likely to be sexually abused. • Characteristics of the children abused, in particular, the differences between male and female children: • Females are at a high risk of child sexual abuse, • Males are more prone to physical abuse. • There is an absence of reported fatal child abuse. • Profile of the alleged perpetrator: • most of the abuse is either intra-familial, or inflicted by a person known to the child. • The geographical distribution of child abuse: • the distribution of abuse is influenced by the reporting agencies. In this study the incidence of reported child abuse and neglect is predominantly from the Cape Flats areas, though this does not reflect the rate of reported child abuse and neglect. • Action is taken by child protection agencies: • the majority of reported child abuse and neglect is managed by social service agencies; • the police do not investigate child reported child abuse and neglect in the majority of cases. • Comparison with the literature: • The characteristics of reported child abuse differ from that in the literature. • Child physical abuse is under-reported in comparison to other countries. • Rates of reported child sexual abuse are higher than those reported in the literature. Conclusions and recommendations Child abuse is an important problem in Cape Town, and in South Africa as a whole. The required response to this phenomenon is the development of an appropriate Child Protection Service, based on the concept of the prevention of child abuse and neglect, rather than on a reaction to abuse already present. This involves consideration of the data in this study and other studies, as well as examination of the philosophy behind the Child Protection Service to be set up. This approach can be adapted in other countries.